2021
DOI: 10.3390/antiox10050777
|View full text |Cite
|
Sign up to set email alerts
|

Novel N,N′-Disubstituted Selenoureas as Potential Antioxidant and Cytotoxic Agents

Abstract: A series of 30 novel N,N disubstituted selenoureas were synthesized, characterized, and their antioxidant ability was tested using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid (ABTS) assays. Additionally, their cytotoxic activity was tested in vitro in a panel of three different cancer (breast, lung and colon) and two normal cell lines. Each selenourea entity contains a para-substituted phenyl ring with different electron-withdrawing and electron-donating groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Considering the aforementioned in vitro and in vivo therapeutic immunomodulatory properties of DSeU 13 and the well-known role played by the selenoureido motif as ROS scavenging, 32 we selected this bioactive sp 2 -IGL as target candidate to perform the proof-of-concept study. The stereoselective synthesis of (1 S )-( N ′-dodecylselenoureido)-5 N ,6 O -oxomethylidenenojirimycin 13 (DSeU, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the aforementioned in vitro and in vivo therapeutic immunomodulatory properties of DSeU 13 and the well-known role played by the selenoureido motif as ROS scavenging, 32 we selected this bioactive sp 2 -IGL as target candidate to perform the proof-of-concept study. The stereoselective synthesis of (1 S )-( N ′-dodecylselenoureido)-5 N ,6 O -oxomethylidenenojirimycin 13 (DSeU, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, molecules that exert both antioxidant and antiproliferative activity have been reported, such as 2,6-diaminopyridine derivatives [42], 1,3,5-trisubstituted aryl-5-hydroxypyrazoline analogues [43], 3,5-bis(arylidene)-4-piperidones [44], and several phosphoramidates containing selenium [45]. Most of them display moderate anticancer activity together with excellent antioxidant capacity [11,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Many organoselenium compounds exhibit antioxidant activity closely correlated to their ability to scavenge reactive oxygen species (ROS) [24]. It was recently shown that selenoureas of the similar structures possess moderate antioxidant activity [25]. Thus, at the further steps, the complex investigation of the target compounds' ability to interact with protons, electrons, and radicals was conducted.…”
Section: Tests On Living Cellsmentioning
confidence: 99%
“…The sample solution (0.1 mL) was mixed with 0.1 mL phosphate buffer (0.2 M, pH 6.6) and 0.1 mL potassium ferricyanide (1%). For each test compound, different concentrations of EtOH were used (5,10,25,50,100,200 and 250 µM). The resulting mixture was incubated at 50 • C for 20 min.…”
Section: Ferric-reducing Antioxidant Power (Frap Assay)mentioning
confidence: 99%